Developmental analysis of a hybrid gene composed of parts of the Ubx and abd-A genes of Drosophila - Casanova, Jordi (1988)
C1 is a mutation in the bithorax complex (BX-C) of Drosophila resulting from the deletion of parts of the Ubx and abd-A genes. We show that the `hybrid' gene formed by the fusion of the remaining parts of Ubx and abd-A (5'abd-A/Ubx3') is functional and developmentally active. It specifies parasegment patterns with a mixture of thoracic and abdominal identities. The hybrid gene also has other properties typical of conventional bithorax genes: it can be spatially derepressed in the absence of trans-acting genes like extra Sex combs or Polycomb and in turn represses other homeotics like Sex combs reduced. The comparison of embryos containing exclusively hybrid gene activity with others having no BX-C function indicates that the hybrid gene is active in the body region defined by PS5 to PS14. The expression in PS5 and PS6 suggests that one control region (abx) of Ubx can regulate the transcription of the abd-A promoter.